Prevalence Of Stress And Its Possible Associated Factors Among Nursing Students In South India – A Cross-Sectional Study - Logesh D, Logesh D; Dorai B, Lakshmi; Babu, Karun; Logesh D, Logesh D (Journal of Neonatal Surgery, 2025)
Background: Demanding clinical and academic environments have been potential sources of stress among nursing students. The levels of stress and anxiety may vary during students’ educational training, depending on their ability to adopt behavioral strategies for coping with stress and other factors. Objectives: To assess the degree of stress among nursing students and identify if any possible factors cause the stress. Methodology: A cross-sectional study was conducted in Vinayaka Missions Annapoorana College of Nursing from October 2023 to April 2024. The study included 280 nursing Students studying in the Vinayaka Missions Annapoorana College of Nursing. The level of stress among the study participants was assessed using Perceived Stress Scale (PSS) for nursing students and College Student’s Stress questionnaire. Results: The average age of the students was 19.9 years old, and 78.3% were females. The majority of the study participants had mild stress (51.4%), 41.8% had a moderate level of stress and 6.8% had a severe level of stress according to the Perceived Stress Scale (PSS). There was a significant association between the age group, gender, academic performance, and level of stress among the study participants (p<0.05). Conclusion: Nursing teachers and clinical mentors should be encouraged to develop programs to help prepare nursing students to cope with the challenges they are about to face during their clinical placements.